Analisis Kepemimpinan Kepala Sekolah dalam Pengelolaan Pendidikan di Sekolah Dasar: Pengabdian - Yanti Yandri Kusuma; Nurhaswinda; Iis Aprinawati; Sumianto; Lusiana Jelita; Rizki Ananda (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the leadership of school principals in managing education at SDN 007 Pulau Lawas. School leadership plays a strategic role in determining the success of educational management, particularly in planning, organizing, implementing, and evaluating school programs. This study employed a qualitative approach using observation, interviews, and documentation as data collection techniques. The findings indicate that the principal has implemented leadership functions in school management; however, several aspects still require improvement, particularly teacher involvement in planning, sustainable academic supervision, and the utilization of evaluation results for decision-making. Strengthening participatory and effective leadership is expected to enhance the quality of educational management in elementary schools.